THE ROLE OF GRAPHIC DESIGN IN STRENGTHENING URBAN ART BRANDING IN THE SOLO IS SOLO ART COMMUNITY - Abiyoga, Taufan Amirullah (Arty: Jurnal Seni Rupa, 2025)
This study examines the role of graphic design in strengthening identity with urban art styles in the Solo Is Solo community in Solo City. In the context of acculturation of modern culture and local traditions, graphic design serves as a visual communication medium that articulates the vision, mission, and unique character of the community through elements such as logos, murals, typography, and digital content. The research method is qualitative descriptive with an in-depth analysis of artworks that reflect the character of urban art. The results show that graphic design not only strengthens the identity of the community internally as a forum for solidarity, but also builds positive recognition and perception in the eyes of the wider public. Graphic design acts as a creative bridge that connects Solo's cultural traditions with modern styles of expression, maintaining cultural relevance through innovation and attractive aesthetics in public spaces. The application of graphic design in urban art also enriches the aesthetic value of the city while opening up opportunities for the development of cultural tourism. This research emphasizes that graphic design is a strategic tool that supports the sustainability and existence of the urban art community in the ever-evolving socio-cultural dynamics. These findings can serve as a reference for other art communities in building a strong and sustainable visual identity.